STUDI LITERATUR MENGENAI DAMPAK PENERAPAN PSAK 73 TERHADAP KOREKSI FISKAL DAN PERPAJAKAN BADAN DI INDONESIA DARI SISI PENYEWA - Akhmad Ryan Dhiya 'Ulhaq (Politeknik Keuangan Negara STAN, 2021)
PSAK 73 is a new standard on lease effective January 1, 2020. PSAK 73 was adopted from IFRS 16 had a major impact on lease transactions for lessees. They are required to classify almost all of their lease transactions as finance lease by showing right of use assets and lease liabilities in statement of financial position. Implementation of PSAK 73 also has an impact on fiscal corrections that need to be made by lessees in calculating taxable income and income tax expense. Lessees discused in this paper is a business entities operating in Indonesia and tax subject in that country. The purpose of writing this paper is to determine application of PSAK 73 in lease transactions and impact on corporate tax including fiscal corrections from the lessees side. Using qualitative research methods : concept analysis, the author conducted a literature study of PSAK 73 and KMK-1169/1991. The author uses secondary data in data processing by providing illustrations in form of case studies about lease transactions to be reviewed from accounting and taxation side. Results of writing this paper show implementation of standards and provisions that are close by conditions in the field.